Quality and safety improvements in informal milk markets and implications for food safety policy - Lapar, Ma. Lucila; Deka, Ram Pratim; Lindahl, Johanna F.; Grace, Delia (2014)
Milk marketing in Assam, NE India remains predominantly in the informal sector; there is also growing concern among consumers about the purity and quality of milk marketed by informal milk vendors and the possible health risk posed by it. ILRI’s study on milk safety (ILRI 2008) indicates that most of the milk samples (including pasteurized and UHT) available in Assam do not meet quality standards from the standpoint of physical quality, adulterants and bacterial load (total bacterial count and coliform count). In 2009, a training and certification program was initiated to improve milk handling among milk traders who are the main conduits of milk being marketed in Assam. The impact of the program on milk value chain actors was assessed through a prospective matched cohort study using a double difference design. Data was collected from surveys of producers, milk vendors, and consumers. Rapid diagnostic tests on milk samples were conducted to assess levels of hazards from presence of pathogens in milk traded in informal milk markets. Estimates of economic benefits show positive effects in terms of increased average profit margins and value added. Sector level benefits as approximated from micro-level estimates of economic indicators show that traditional dairy value chain in Kamrup generates about 0.8 million rupees value added per day; this translates to an annual estimate of economic impact in Kamrup of at least US$ 5.6 million. Given the important economic contribution of traditional dairy value chain, public policy that affects informal milk markets and actors will need to be based on risk and not hazard, and improving capacity for risk assessment and incentives for better risk management will support the continued viability of the traditional dairy sector in Assam. Keywords: smallholder dairy, informal milk markets, food safety policy